Factors Affecting Job Satisfaction Among Agency-Employed Home Health Aides. (February 2016) - Yoon, Seokwon; Probst, Janice; DiStefano, Christine
To examine the predictors of job satisfaction by home health aides, we conducted structural equation modeling to identify how the predicting variables directly and indirectly influence job satisfaction by home health aides. A total of 3, 274 female home health aides working in home health care industry were selected for this study from the nationally representative sample. Support from organizations and supervisors, and personal support have positive direct effects on the job satisfaction of home health aides. Organizational support and supervisor support have important roles in weakening the negative relationship between job-related stressors and job satisfaction. We conclude that support from organizations and supervisors might improve job satisfaction by home health aides through reducing stress.